Characteristics of interventions in cardiac surgery in a general hospital of Lima, Peru - Salamanca, Max A. (2023)
Objective: To describe the clinical, epidemiological, and surgical characteristics of cardiac interventions in a general hospital in Lima, Peru. Methods: a retrospective and descriptive study was carried-out at Hospital Maria Auxiliadora from 2009-2019, 41 patients were included. Results: Median age was 44 years (IQR: 26.5-58.5); 75.6% were females. Underlying conditions were arrhythmias (56.1%); blood hypertension (36.6%); strokes (24.4%) and diabetes (14.6%). Valve replacement using prosthetic valves was the most frequent procedure (39%), mainly mitral valve replacement; followed by surgical repairs of septum abnormalities, mainly atrial defects (26.8%). The most common post-operative complications were nosocomial pneumonia (14%), new arrhythmia (14%) and low output syndrome (12%). Mean times of extracorporeal circulation and aortic clamping were 97.5 ± 39.0 min and 68.1 ± 35.5 min, respectively. Mean ICU and hospital stays were 4.1 ± 2.9 and 22.3 ± 10.9 days, respectively. No fatalities were recorded 30-days after the procedures. Conclusions: Young, predominantly female adults with significant comorbidities were surgically intervened in this setting. The main surgical procedure was valve replacement, no differences with reports from Latin America were found.